Coronavirus Disease-2019: A Threat to Global Peace and Security - RUKUNI, Tinashe; KANSIIME, Noel; COLLIN, Asani; OYINLOYE, Olaoluwa Babatunde A. (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2024)
The outbreak of the “Coronavirus disease 2019” on a worldwide basis has brought about an unprecedented threat to the already fragile global peace and security position. The epidemic has had catastrophic social, economic, and political consequences on a global scale. The global pandemic which originated in the Chinese city of Wuhan in December 2019 has become a source of serious international debate, a humanitarian crisis of fearsome proportions, and sparked conflict among the world’s major powers. It is against this background and perturbing development that this paper interrogates the implications of Coronavirus disease 2019 as a threat to global peace and security. Thus, the fulcrum of the ensuing discourse is anchored on the examination of the post-Covid-19 outbreak humanitarian crisis, surge in domestic violence in lockdown periods the world over, the imminent world economic recession, food insecurity, revival of xenophobia related violence and the ignition of geopolitical conflict mainly among the world’s major economic and political powers. The paper was based on the qualitative research paradigm, as it sought to probe deep into contemporary issues around the novel Covid-19 pandemic. The paper found out that Covid-19 is a serious threat to global peace and security and has also perpetuated a global humanitarian crisis, gender-based, economic recession violence, and xenophobia. Based on the salient findings and major conclusions reached the paper ends by proffering recommendations tailored to promote global peace and security in the aftermath of the Covid-19 outbreak.